2023
DOI: 10.21676/23897856.4612
|View full text |Cite
|
Sign up to set email alerts
|

Prácticas de enseñanza con primera infancia durante el Covid-19. Relato de la emergencia de los ambientes virtuales en educación inicial

Zaily del Pilar García Gutiérrez,
Ángela Patrica Durán Pérez,
Nelly Johanna Sánchez Quijano

Abstract: Este artículo presenta los resultados de una investigación cuyo propósito fue visibilizar los ambientesvvirtuales emergentes en las prácticas de docentes de educación inicial en una institución educativa oficial de Bogotá, Colombia, enfrentando el desafío de la mejora y actualización permanente, exacerbado por la pandemia de COVID-19. La metodología adoptada fue la investigación cualitativa con un enfoque crítico social, utilizando el método biográfico narrativo para co-crear historias de vida a partir de micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Even though this option seemed initially feasible, it revealed inequalities within the country regarding internet accessibility and the availability of devices in vulnerable places. Zoom and Meet require both high internet speeds and storage space, increasing barriers to access virtual education for people in low socio-economic strata and complicating the linking of rural areas; thus, the need for other alternatives and devices to reach a wider population has become vital (García Gutiérrez et al, 2023). The government, in collaboration with local educational institutions, concluded that most of the population (119% of them) has a mobile device in their homes (Medina, 2020), which encouraged the integration of smartphones in most educational institutions using applications or platforms like WhatsApp as a way to transfer synchronous sessions to asynchronous ones, making it the most suitable alternative for rural schools and low-income students to advance their learning processes (Domenech Pantoja et al,2023).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this option seemed initially feasible, it revealed inequalities within the country regarding internet accessibility and the availability of devices in vulnerable places. Zoom and Meet require both high internet speeds and storage space, increasing barriers to access virtual education for people in low socio-economic strata and complicating the linking of rural areas; thus, the need for other alternatives and devices to reach a wider population has become vital (García Gutiérrez et al, 2023). The government, in collaboration with local educational institutions, concluded that most of the population (119% of them) has a mobile device in their homes (Medina, 2020), which encouraged the integration of smartphones in most educational institutions using applications or platforms like WhatsApp as a way to transfer synchronous sessions to asynchronous ones, making it the most suitable alternative for rural schools and low-income students to advance their learning processes (Domenech Pantoja et al,2023).…”
Section: Introductionmentioning
confidence: 99%